Hydroxychloroquine Induced DRESS (Drug Rash with Eosinophilia and Systemic Symptoms Syndrome) Mimicking SARS-COV-2 Illness: A Case Report with Review - Patel, Maitri M.; Patel, Dhruvkumar M.; Patel, Mukundkumar V.; Gurumukhani, Jayanti K.; Patel, Suyog Y; Patel, Harsh D. (Coronaviruses, 2021)
Background: In the current pandemic of COVID-19, hydroxychloroquine (HCQ) is recommended as an experimental drug for prophylaxis and treatment of the illness. Although it is a safe drug, it can rarely produce a severe drug reaction ‘drug rash with eosinophilia and systemic symptoms syndrome (DRESS)’, and to differentiate it from systemic viral infections is challenging. Case Presentation: A 45-year old male nurse working in a COVID-19 ward consumed HCQ weekly for two weeks for prevention of SARS-COV-2 illness. He presented with fever, pruritic maculopapular palmar rash, cervical lymphadenopathy for 12 hours and was quarantined as a suspected COVID-19 case. His laboratory tests revealed lymphopenia, eosinophilia, atypical lymphocytes, raised liver enzymes along with IgM negative, IgG positive rapid antibody test of SARS-COV-2. However, his throat swabs for SARS-COV-2 by real-time PCR were negative on day 1 and 7. He was finally diagnosed as definite DRESS based on the RegiSCAR score of six. He responded to levocetirizine 5 mg OD and oral prednisolone 60 mg daily tapered over 7 days. Conclusion: DRESS due to HCQ is ‘probable’, ‘of moderate severity’, and ‘not preventable’ adverse effect mimicking SARS-COV-2 illness.
Keywords: drug rash with eosinophilia and systemic symptoms